How to charge a secondary battery
By adopting a multi-stage charging method during the charging process of lithium-ion batteries, including the first charging step of controlling the SOC of no more than 4.5%, the problem of internal short circuit of the lithium-ion battery is solved, significantly improving the safety and reliability of the battery.
Patent Information
- Application Number
- JP2023570473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-27
- Filing Date
- 2022-12-16
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-12-16
AI Technical Summary
The prior art is difficult to fully suppress the internal short circuit problem of lithium-ion batteries during charging, especially dendrites due to precipitation of lithium metal.
A multi-stage charging method is adopted, including a first charging step and a second charging step. In the first charging step, the growth of dendrites is inhibited by at least one pause or discharge and the battery state charge (SOC) is controlled to not exceed 4.5%.
It effectively suppresses the occurrence of short circuits in lithium-ion batteries and improves the safety and reliability of the batteries.
Smart Images

Figure 0007663135000002 
Figure 0007663135000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for charging a secondary battery. [Background technology]
[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there is hope that the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs) will help reduce carbon dioxide emissions, and there has been active development of secondary batteries, such as motor drive secondary batteries, which hold the key to putting these vehicles to practical use.
[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.
[0004] Currently, lithium secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and these liquid-based lithium secondary batteries require stricter safety measures against leakage, short circuits, overcharging, etc. than other batteries.
[0005] In recent years, research and development of all-solid-state lithium secondary batteries using oxide- or sulfide-based solid electrolytes has been actively conducted. A solid electrolyte is a material that is mainly composed of ion conductors that can conduct ions in a solid state. Therefore, in principle, all-solid-state lithium secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery. All-solid-state lithium secondary batteries that use sulfide-based materials as the positive electrode active material and metallic lithium or lithium-containing alloys as the negative electrode active material are promising candidates.
[0006] In a lithium secondary battery, the negative electrode potential decreases as the charging process proceeds. + ), metallic lithium precipitates in the negative electrode, forming dendrites (branch-like crystals) (this phenomenon is also called the electrodeposition of metallic lithium). When metallic lithium precipitates, the precipitated dendrites penetrate the solid electrolyte layer, causing an internal short circuit in the battery.
[0007] For example, JP 2020-009724 A discloses a charging method for a secondary battery that utilizes a deposition-dissolution reaction of metallic lithium as a negative electrode reaction for the purpose of simultaneously suppressing short circuits in the battery and shortening the charging time. The charging method includes a first charging step of charging the secondary battery at a first current density I1, and a second charging step of charging the secondary battery at a second current density I2 greater than the first current density I1 after the first charging step. The first charging step is characterized in that the secondary battery is charged at a first current density I1 until X / Y becomes 0.5 or more, where Y (μm) is the roughness height on the negative electrode current collector foil side surface of the solid electrolyte layer and X (μm) is the thickness of the roughness coating layer. Summary of the Invention
[0008] However, according to the studies of the present inventors, it was found that when the charging method described in JP 2020-009724 A is applied to a secondary battery, there are cases in which a short circuit in the battery cannot be sufficiently suppressed.
[0009] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a means for further suppressing short circuits in secondary batteries.
[0010] The present inventors have conducted intensive research to solve the above problems. As a result, in the charging step corresponding to the "first charging step" described in JP 2020-009724 A, the inventors have found that the above SOC problem can be solved by performing at least one pause and / or discharge and charging so that the (State of Charge) does not exceed 4.5%, and have completed the present invention. In this specification, the uncharged state is defined as SOC 0%, and the state in which the battery is charged at a constant current and then charged at a constant voltage after reaching 4.2 V, and the current value is 20% or less of the constant current value is defined as SOC 100%.
[0011] One embodiment of the present invention relates to a method for charging a secondary battery having a positive electrode current collector, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector in this order, and utilizing a deposition-dissolution reaction of metallic lithium as a reaction of the negative electrode. The charging method includes a multi-step charging process including at least a first charging process and a second charging process. The first charging process is a process for charging the secondary battery at a first current density I1 to deposit metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector, thereby forming a deposited Li layer that is a part of the negative electrode active material layer and is made of the metallic lithium. The second charging process is a process for charging the secondary battery at a second current density I2 that is larger than the first current density I1 after the first charging process, thereby increasing the thickness of the deposited Li layer. The first charging process includes at least one pause or at least one discharge, and is characterized in that the secondary battery is charged at the first current density I1 so that the SOC does not exceed 4.5%. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a flat laminate-type all-solid-state lithium secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described with reference to the attached drawings. However, the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following forms. In the description of the drawings, the same elements are given the same symbols, and duplicated explanations are omitted. In addition, the dimensional ratios of the drawings are exaggerated for the convenience of explanation, and may differ from the actual ratios. In this specification, the numerical range "A to B" means "A or more and B or less." "A and / or B" means "either A or B" or "both A and B."
[0014] One embodiment of the present invention relates to a method for charging a secondary battery having a positive electrode current collector, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector in this order, and utilizing a deposition-dissolution reaction of metallic lithium as a reaction of the negative electrode. The charging method includes a multi-step charging process including at least a first charging process and a second charging process. The first charging process is a process for charging the secondary battery at a first current density I1 to deposit metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector, thereby forming a deposited Li layer that is a part of the negative electrode active material layer and is made of the metallic lithium. The second charging process is a process for charging the secondary battery at a second current density I2 that is larger than the first current density I1 after the first charging process, thereby increasing the thickness of the deposited Li layer. The first charging process includes at least one pause or at least one discharge, and is characterized in that the secondary battery is charged at the first current density I1 so that the SOC does not exceed 4.5%. According to the charging method of the present embodiment, it is possible to further prevent short-circuiting of the secondary battery.
[0015] First, a secondary battery to which the charging method according to the present embodiment is applied will be described. Fig. 1 is a cross-sectional view showing a flat-laminated all-solid-state lithium secondary battery according to one embodiment of the present invention. In this specification, a flat-laminated non-bipolar lithium secondary battery (hereinafter, also simply referred to as a "laminated secondary battery") shown in Fig. 1 will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the all-solid-state lithium secondary battery according to the present embodiment, the method can be applied to both non-bipolar (internal parallel connection type) batteries and bipolar (internal series connection type) batteries.
[0016] As shown in FIG. 1, the stacked secondary battery 10a of this embodiment has a structure in which a flat, generally rectangular power generating element 21, where the charge and discharge reactions actually proceed, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. The positive electrode is formed by applying a positive electrode active material (here, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 The negative electrode has a structure in which a negative electrode active material layer 15 (a deposited Li layer made of metallic lithium as a negative electrode active material) containing a negative electrode active material is disposed on both sides of a negative electrode current collector 11". Specifically, the positive electrode, the solid electrolyte layer, and the negative electrode are laminated in this order such that one positive electrode active material layer 13 and an adjacent negative electrode active material layer 15 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute one single cell layer 19. Therefore, it can be said that the stacked type secondary battery 10a shown in FIG. 1 has a structure in which a plurality of single cell layers 19 are laminated and electrically connected in parallel.
[0017] 1, the outermost positive electrode current collectors located on both outermost layers of the power generating element 21 each have a positive electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. In other words, instead of using a current collector exclusively for the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as it is as the outermost layer current collector.
[0018] Positive current collector 11' and negative current collector 11" are respectively attached with positive current collector (tab) 25 and negative current collector (tab) 27 that are electrically connected to the respective electrodes (positive and negative electrodes), and are structured so as to be sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Positive current collector 25 and negative current collector 27 may be respectively attached to positive current collector 11' and negative current collector 11" of each electrode by ultrasonic welding, resistance welding, or the like via positive lead and negative lead (not shown) as necessary. Note that a restraining pressure is applied to stacked secondary battery 10a in the stacking direction of power generating element 21 by a pressure member (not shown). Therefore, the volume of power generating element 21 is kept constant.
[0019] Hereinafter, the main components of the all-solid-state lithium secondary battery according to this embodiment will be described.
[0020] [Positive electrode current collector] The positive electrode current collector is a conductive member that functions as a flow path for electrons that are discharged from the positive electrode toward an external load or flow from a power source toward the positive electrode as the battery reaction (charge / discharge reaction) progresses. There are no particular limitations on the material that constitutes the positive electrode current collector. For example, metals and conductive resins can be used as the material that constitutes the positive electrode current collector.
[0021] Specifically, examples of metals include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition, clad materials of nickel and aluminum, clad materials of copper and aluminum, and the like may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, and the like. In addition, examples of the latter conductive resin include resins in which a conductive filler is added to a non-conductive polymer material.
[0022] The current collector may be a single layer structure made of a single material, or may be a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector includes at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector.
[0023] The thickness of the positive electrode current collector is not particularly limited, but is, for example, 10 to 100 μm.
[0024] [Cathode active material layer] The positive electrode active material layer includes a positive electrode active material. The type of the positive electrode active material is not particularly limited, but may be a layered rock salt type active material such as LiCoO2, LiMnO2, LiNiO2, LiVO2, or Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of oxide active materials other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12 Among them, a composite oxide containing lithium and nickel is preferably used, and more preferably Li(Ni-Mn-Co)O2 and those in which a part of these transition metals is replaced by other elements (hereinafter, also simply referred to as "NMC composite oxide"). NMC composite oxides have a layered crystal structure in which lithium atomic layers and transition metal (Mn, Ni, and Co arranged in an orderly manner) atomic layers are alternately stacked with oxygen atomic layers interposed therebetween, and one Li atom is contained per atom of the transition metal M. The amount of Li that can be extracted is twice that of spinel-based lithium manganese oxides, that is, the supply capacity is doubled, and high capacity can be obtained.
[0025] As described above, the NMC composite oxide also includes composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc., preferably Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and even more preferably Ti, Zr, Al, Mg, Cr from the viewpoint of improving cycle characteristics.
[0026] Furthermore, a sulfur-based positive electrode active material is also used in one of the preferred embodiments. Examples of the sulfur-based positive electrode active material include particles or thin films of organic sulfur compounds or inorganic sulfur compounds, and any material may be used as long as it can release lithium ions during charging and absorb lithium ions during discharging by utilizing the oxidation-reduction reaction of sulfur. Examples of the organic sulfur compound include disulfide compounds, sulfur-modified polyacrylonitrile, sulfur-modified polyisoprene, rubeanic acid (dithiooxamide), polycarbonate sulfide, and the like, which are typified by compounds described in the pamphlet of International Publication No. 2010 / 044437. Among these, disulfide compounds, sulfur-modified polyacrylonitrile, and rubeanic acid are preferred, and sulfur-modified polyacrylonitrile is particularly preferred. As the disulfide compound, those having a dithiobiurea derivative, a thiourea group, a thioisocyanate, or a thioamide group are more preferred. Here, the sulfur-modified polyacrylonitrile is a modified polyacrylonitrile containing sulfur atoms, which is obtained by mixing sulfur powder with polyacrylonitrile and heating the mixture under an inert gas or under reduced pressure. Its estimated structure is, for example, as shown in Chem. Mater. 2011, 23, 5024-5028, in which polyacrylonitrile is ring-closed to form a polycyclic ring, and at least a part of S is bonded to C. The compound described in this document has a peak at 1330 cm in the Raman spectrum. -1 and 1560cm -1 There is a strong peak signal near 307 cm -1 , 379cm -1, 472cm -1 , 929cm -1 There is a peak around 1000 nm. On the other hand, inorganic sulfur compounds are preferred because of their excellent stability, and specific examples thereof include sulfur (S), S-carbon composite, TiS2, TiS3, TiS4, NiS, NiS2, CuS, FeS2, Li2S, MoS2, and MoS3. Among them, S, S-carbon composite, TiS2, TiS3, TiS4, FeS2, and MoS2 are preferred, and S-carbon composite, TiS2, and FeS2 are more preferred. Here, the S-carbon composite is a composite state that contains sulfur powder and a carbon material and is subjected to a heat treatment or mechanical mixing. More specifically, it is a state in which sulfur is distributed on the surface or in the pores of the carbon material, a state in which sulfur and the carbon material are uniformly dispersed at the nano level and aggregated to form particles, a state in which the carbon material is distributed on the surface or inside of fine sulfur powder, or a state in which a plurality of these states are combined.
[0027] In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, positive electrode active materials other than the above may be used. The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within the range of 35 to 99 mass%, and more preferably within the range of 40 to 90 mass%, for example.
[0028] The positive electrode active material layer preferably further contains a solid electrolyte. By containing the solid electrolyte in the positive electrode active material layer, the ionic conductivity of the positive electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes, and from the viewpoint of high ionic conductivity, it is preferable to contain a sulfide solid electrolyte.
[0029] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0030] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. Examples of sulfide solid electrolytes having a Li4P2S7 skeleton include Li-PS solid electrolytes called LPS (for example, Li7P3S 11 ) As the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P xAn LGPS or the like represented by S4 (where 0 < x < 1) may be used. Among them, the sulfide solid electrolyte is preferably a sulfide solid electrolyte containing P element, and more preferably a material mainly composed of Li2S-P2S5. Furthermore, the sulfide solid electrolyte may contain a halogen (F, Cl, Br, I).
[0031] Also, when the sulfide solid electrolyte is of the Li2S-P2S5 system, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 100:0 in molar ratio, and more preferably Li2S:P2S5 = 70:30 to 80:20.
[0032] Also, the sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid-phase method. The sulfide glass can be obtained, for example, by performing mechanical milling (such as a ball mill) on a raw material composition. Also, the crystallized sulfide glass can be obtained, for example, by heat-treating the sulfide glass at a temperature above the crystallization temperature. Also, the ionic conductivity (for example, Li ion conductivity) of the sulfide solid electrolyte at room temperature (25 °C) is, for example, 1×10 -5 S / cm or more, and more preferably 1×10 -4 S / cm or more. The value of the ionic conductivity of the solid electrolyte can be measured by an alternating current impedance method.
[0033] Examples of the oxide solid electrolyte include compounds having a NASICON-type structure. As an example of a compound having a NASICON-type structure, a compound represented by the general formula Li 1+x Al x Ge 2-x (PO4)3 (0 ≤ x ≤ 2) (LAGP), a compound represented by the general formula Li 1+x Al x Ti 2-x (PO4)3 (0 ≤ x ≤ 2) (LATP), etc. are mentioned. Also, as another example of the oxide solid electrolyte, LiLaTiO (for example, Li0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.
[0034] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, the average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50 ) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.
[0035] The content of the solid electrolyte in the positive electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.
[0036] The positive electrode active material layer may further contain at least one of a conductive assistant and a binder, in addition to the above-mentioned positive electrode active material and solid electrolyte.
[0037] Examples of the conductive assistant include metals such as aluminum, stainless steel (SUS), silver, gold, copper, and titanium, alloys or metal oxides containing these metals; carbon fibers (specifically, vapor-grown carbon fibers (VGCF), polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, rayon-based carbon fibers, activated carbon fibers, etc.), carbon nanotubes (CNTs), and carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.), but are not limited thereto. In addition, a particulate ceramic material or a resin material coated with the above-mentioned metal material by plating or the like can also be used as a conductive assistant. Among these conductive assistants, from the viewpoint of electrical stability, it is preferable to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium, and carbon, more preferably to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, and carbon, and even more preferably to include at least one carbon. These conductive assistants may be used alone or in combination of two or more.
[0038] The conductive assistant is preferably in the form of particles or fibers. When the conductive assistant is in the form of particles, the shape of the particles is not particularly limited, and may be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, scale, spindle shape, etc.
[0039] When the conductive assistant is particulate, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably 0.01 to 10 μm from the viewpoint of the electrical properties of the battery. In this specification, the "particle diameter of the conductive assistant" means the maximum distance L between any two points on the contour line of the conductive assistant. The value of the "average particle diameter of the conductive assistant" is calculated as the average value of particle diameters of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0040] When the positive electrode active material layer contains a conductive assistant, the content of the conductive assistant in the positive electrode active material layer is not particularly limited, but is preferably 0 to 10 mass%, more preferably 2 to 8 mass%, and further preferably 4 to 7 mass% relative to the total mass of the positive electrode active material layer. If the content is within such a range, a stronger electron conduction path can be formed in the positive electrode active material layer, which can effectively contribute to improving the battery characteristics.
[0041] On the other hand, the binder is not particularly limited, but examples thereof include the following materials:
[0042] Thermoplastic polymers such as polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are replaced by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene-butadiene rubber (SBR), ethylene-propylene-diene copolymer, styrene-butadiene-styrene block copolymer and its hydrogenated derivatives, styrene-isoprene-styrene block copolymer and its hydrogenated derivatives, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene Examples of such fluororesins include ethylene-chlorotrifluoroethylene copolymer (ECTFE) and polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), and vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber), as well as epoxy resins. Among these, polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, and polyamide are more preferable.
[0043] The thickness of the positive electrode active material layer varies depending on the intended configuration of the all-solid-state battery, but is preferably within the range of, for example, 0.1 to 1000 μm, and more preferably 40 to 100 μm.
[0044] [Solid electrolyte layer] The solid electrolyte layer is a layer that contains a solid electrolyte as a main component and is interposed between the negative electrode active material layer and the positive electrode active material layer. The specific form of the solid electrolyte contained in the solid electrolyte layer is the same as that described above, so a detailed description will be omitted here.
[0045] The content of the solid electrolyte in the solid electrolyte layer is, for example, preferably in the range of 10 to 100 mass %, more preferably in the range of 50 to 100 mass %, and further preferably in the range of 90 to 100 mass %.
[0046] The solid electrolyte layer may further contain a binder in addition to the above-mentioned solid electrolyte. The specific form of the binder that can be contained in the solid electrolyte layer is the same as that described above, and therefore a detailed description thereof will be omitted here.
[0047] The thickness of the solid electrolyte layer varies depending on the configuration of the intended all-solid-state battery, but from the viewpoint of improving the volumetric energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. On the other hand, there is no particular restriction on the lower limit of the thickness of the solid electrolyte layer, but it is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more.
[0048] [Negative electrode current collector] The negative electrode current collector is a conductive member that functions as a flow path for electrons that are discharged from the negative electrode toward the power source as the battery reaction (charge / discharge reaction) progresses, or that flow from an external load toward the negative electrode. There are no particular limitations on the material that constitutes the negative electrode current collector. As with the positive electrode current collector, metals and conductive resins can be used as the material that constitutes the negative electrode current collector. There are no particular limitations on the thickness of the negative electrode current collector, but an example is 10 to 100 μm.
[0049] [Negative electrode active material layer] The all-solid-state battery according to the present embodiment is a so-called lithium deposition type battery in which lithium metal is deposited on the negative electrode current collector during charging. The layer (deposited Li layer) made of lithium metal deposited on the negative electrode current collector during this charging process is the negative electrode active material layer of the lithium secondary battery according to the present embodiment. Therefore, the thickness of the negative electrode active material layer increases with the progress of the charging process, and the thickness of the negative electrode active material layer decreases with the progress of the discharging process. The thickness of the negative electrode active material layer (lithium metal layer) at the time of full charging is not particularly limited, but is usually 0.1 to 1000 μm.
[0050] [Positive and negative leads] Although not shown in the figure, the current collector and the current collector plate may be electrically connected via a positive electrode lead and a negative electrode lead. As the constituent materials of the positive electrode and the negative electrode lead, materials used in known lithium secondary batteries may be similarly adopted. Note that the part taken out from the exterior is preferably covered with a heat-resistant insulating heat shrink tube or the like so as not to come into contact with peripheral devices or wiring, causing leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).
[0051] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum that can cover the power generating element can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, since the group pressure applied from the outside to the power generating element can be easily adjusted, a laminate film containing aluminum is more preferable as the exterior body.
[0052] The stacked secondary battery according to the present embodiment has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has high capacity and excellent cycle durability, and is therefore suitable for use as a driving power source for EVs and HEVs.
[0053] [Charging method] Next, the charging method of the secondary battery according to the present embodiment will be described. The charging method of the secondary battery according to the present embodiment includes at least a first charging step in which the secondary battery is charged at a first current density I1 to deposit metallic lithium on the surface of the negative electrode current collector on the side of the solid electrolyte layer, thereby forming a deposited Li layer that is a part of the negative electrode active material layer and is made of the metallic lithium, and a second charging step in which the secondary battery is charged at a second current density I2 larger than the first current density I1 after the first charging step to increase the thickness of the deposited Li layer, the first charging step including at least one pause or at least one discharge, and the secondary battery is charged at the first current density I1 so that the SOC does not exceed 4.5%, which is a multi-stage charging step.
[0054] The mechanism by which the above-mentioned configuration effectively suppresses short-circuiting of the battery (particularly, short-circuiting caused by the deposition and growth of dendrites) is not completely clear, but the following mechanism is presumed. That is, the solid electrolyte layer and the negative electrode current collector of the all-solid-state lithium secondary battery according to the present embodiment are both solid and have some unevenness on the surface, so that they are in contact with each other in a point-to-point state before the first charge. When the first charge is started, lithium is deposited in the space between the solid electrolyte layer and the negative electrode active material layer, starting from the contact point where the solid electrolyte layer and the negative electrode current collector are in contact. At this time, since electric charge is concentrated at the contact point, dendrites are deposited and grow from the contact point toward the positive electrode, and may penetrate the solid electrolyte layer and cause a short circuit. In the charging method according to the present embodiment, in the first charging step, charging is performed at a relatively small current density I1 until the SOC does not exceed 4.5%, thereby preventing the rapid growth of dendrites starting from the contact point. In addition, the concentration of electric charge can be alleviated by pausing the charging. Alternatively, by discharging instead of or in addition to pausing, the grown dendrites can be dissolved and the dendrite path can be cut. By performing such a first charging step, it is possible to suppress the formation of fine dendrites that can grow by subsequent charging at a relatively large current density I2. As a result, it is possible to further suppress short-circuiting of the secondary battery. According to the conventional technology described in the above-mentioned JP 2020-009724 A, charging is performed until the SOC becomes about 4.7% or more in the first charging step. As a result of the investigation by the present inventors, if charging is performed until the SOC exceeds 4.5% in the first charging step, the formation of fine dendrites cannot be sufficiently suppressed even if pausing or discharging is performed, and short-circuiting of the secondary battery may not be sufficiently suppressed. In other words, according to the charging method for a secondary battery according to the present embodiment, the number of fine dendrites on the surface of the solid electrolyte layer side of the precipitated Li layer formed in the first charging step can be reduced (the surface of the solid electrolyte layer side of the precipitated Li layer can be formed more smoothly). Therefore, it is possible to suppress short circuits more significantly than the conventional technology described in JP 2020-009724 A.
[0055] Each step will be described in detail below.
[0056] (First charging process) In the first charging step, the secondary battery is charged at a first current density I1 to deposit metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector, thereby forming a deposited Li layer which is a part of the negative electrode active material layer and is made of the metallic lithium. The first charging step includes at least one rest period or at least one discharge period, and is characterized in that the secondary battery is charged at the first current density I1 so that the SOC does not exceed 4.5%.
[0057] The first current density I1 is not particularly limited as long as it is smaller than the second current density I2 in the second charging step described below, but is preferably 0.22 (mA / cm 2 ), more preferably less than 0.01 (mA / cm 2 ) or more 0.21(mA / cm 2 ) or less, and more preferably 0.02 (mA / cm 2 ) or more 0.10(mA / cm 2 The first current density I1 is 0.22 (mA / cm 2 When the first current density I1 is less than 0.01 (mA / cm 2 ), the deposition and growth of dendrites is less likely to occur, and the effect of suppressing short circuits in the secondary battery is further enhanced. 2 ) or more, the charging time can be shortened.
[0058] The charge rate (C) in the first charging step (the charge rate (C) when the secondary battery is charged at the first current density I1) is preferably less than 0.05 (C), more preferably 0.0023 (C) or more and 0.048 (C) or less, and even more preferably 0.0045 (C) or more and 0.023 (C) or less. When the charge rate (C) is less than 0.05 (C), the precipitation and growth of dendrites is less likely to occur, and the effect of suppressing short circuits in the secondary battery is further enhanced. When the charge rate (C) is 0.0023 (C) or more, the charging time can be shortened. Note that 1C is a current value at which the battery is fully charged (100% charged) when charged at that current value for one hour.
[0059] In this embodiment, the first charging step includes at least one rest period or at least one discharge period.
[0060] Here, "rest" refers to a state in which charging and discharging are not taking place. When resting is performed, the rest time per one rest is not particularly limited, but is preferably 0.005 hours (18 seconds) or more, more preferably 0.01 hours (36 seconds) or more, and even more preferably 0.02 hours (72 seconds) or more. When the rest time is 0.01 hours (36 seconds) or more, the concentration of electric charge is further alleviated, and the effect of suppressing short circuit of the secondary battery is further enhanced.
[0061] The upper limit of the rest time is not particularly limited, but is usually 3 hours or less, preferably 2 hours or less, and more preferably 1.5 hours or less. The number of rests is also not particularly limited, but is usually 1 to 10 times, and preferably 3 to 5 times. When the number of rests is 3 to 5 times, the concentration of charge is further alleviated, and the effect of suppressing short circuit of the secondary battery is further enhanced. In addition, in the case where the discharge described later is included, in addition to the rest during or after charging, or instead of the rest during or after charging, it is preferable to perform a rest after discharging. In addition to the rest during or after charging, the number of rests when performing a rest after discharging is usually 1 to 20 times, and preferably 6 to 10 times.
[0062] When discharging, the lower limit voltage of discharge (cut-off voltage, discharge end voltage) is not particularly limited, but is preferably 0 to 2.5 V, more preferably 2.0 to 2.5 V, and even more preferably 2.3 to 2.5 V. If the lower limit voltage of discharge is 2.5 V or less, the dendrite path can be sufficiently cut, so that the effect of suppressing short circuit of the secondary battery is further enhanced. Even if the battery is discharged until the lower limit voltage of discharge becomes 0 V, a slight precipitated Li layer remains between the solid electrolyte layer and the negative electrode current collector. Since the remaining precipitated Li layer is a layer in which the formation of fine dendrites is suppressed by discharging, even if charging is performed at a relatively large charge density I2 in the subsequent second charging step, the secondary battery is less likely to short circuit compared to the conventional technology described in JP 2020-009724 A.
[0063] The current density and discharge rate during discharge are not particularly limited, and may be approximately the same as the first current density and charge rate in the first charging step. That is, the current density during discharge is preferably 0.22 (mA / cm 2 ), more preferably less than 0.01 (mA / cm 2 ) or more 0.21(mA / cm 2 ) or less, and more preferably 0.02 (mA / cm 2 ) or more 0.10(mA / cm 2 The discharge rate (C) during discharge is preferably less than 0.05(C), more preferably 0.0023(C) or more and 0.048(C) or less, and even more preferably 0.0045(C) or more and 0.023(C) or less.
[0064] The number of discharges is not particularly limited, but is usually 1 to 10, and preferably 3 to 5. When the number of discharges is 3 to 5, the concentration of charge is further alleviated, and the effect of suppressing short circuits in the secondary battery is further enhanced.
[0065] In the first charging step, it is essential to perform at least one pause or at least one discharge, but from the viewpoint of more effectively suppressing the formation of fine dendrites, it is preferable to perform at least one discharge, and more preferably to perform at least one pause and at least one discharge. When performing both pause and discharge, it is preferable to perform a pause between charging and discharging. In addition, when performing pause and / or discharge multiple times in the first charging step, for example, a cycle of "charging, then pausing and / or discharging" may be repeated. In this case, the charging conditions, pause conditions and / or discharge conditions may be the same or different, but considering the ease of operation, it is preferable that the charging conditions, pause conditions and / or discharge conditions are the same. The final operation in the first charging step may be any of charging, pause and discharge.
[0066] In this embodiment, the secondary battery is also characterized in that in the first charging step, the secondary battery is charged at a first current density I1 so that the SOC does not exceed 4.5%. When charging is performed multiple times in the first charging step, charging is performed so that the SOC does not exceed 4.5% in each charging (that is, the SOC does not exceed 4.5% in the first charging step). As described above, if charging is performed until the SOC exceeds 4.5% as in the conventional technology described in JP 2020-009724 A, the formation of fine dendrites cannot be sufficiently suppressed even when pauses and discharges are performed, and short circuits of the secondary battery may not be sufficiently suppressed. The SOC at the end of the first charging step must be 4.5% or less, but is preferably 0.5 to 3.0%, and more preferably 1.0 to 2.0%.
[0067] (Second charging process) In the second charging step, the secondary battery is charged at a second current density I2 that is larger than the first current density I1, thereby increasing the thickness of the deposited Li layer.
[0068] The second current density I2 is not particularly limited as long as it is greater than the first current density I1 in the first charging step (if there are multiple first current densities I1, the largest one among them), but is preferably 0.22 (mA / cm 2 ) or more, and more preferably 0.22 to 1.00 (mA / cm 2 The second current density I2 is 0.22 (mA / cm 2 When the second current density I2 is 1.00 (mA / cm 2 ), the charging time can be shortened. 2 ) or less, precipitation and growth of dendrites are less likely to occur, and the effect of suppressing short circuits in the secondary battery is further improved.
[0069] The charge rate (C) in the second charging step (the charge rate (C) when the secondary battery is charged at the second current density I2) is preferably 0.05 (C) or more, and more preferably 0.05 to 0.23 (C). When the charge rate (C) is 0.05 (C) or more, the charging time can be shortened. When the charge rate (C) is 0.23 (C) or less, precipitation and growth of dendrites are less likely to occur, and the effect of suppressing short circuits in the secondary battery is further improved.
[0070] The method for charging a secondary battery according to the present embodiment is preferably carried out during the first charge, and may be carried out during the second or subsequent charge, as necessary.
[0071] The following embodiments are also included within the scope of the present invention: a method for charging a secondary battery as defined in claim 1 having the features of claim 2; a method for charging a secondary battery as defined in claim 1 or 2 having the features of claim 3; and a method for charging a secondary battery as defined in any of claims 1 to 3 having the features of claim 4. EXAMPLES
[0072] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.
[0073] <<Preparation of test cells (all-solid-state lithium secondary batteries)>> (Preparation of positive electrode) The positive electrode active material layer is made of NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2), an argyrodite-type solid electrolyte (Li6PS5Cl, average particle size (D50) 0.8μm) which is a lithium ion conductive halogen-containing sulfide solid electrolyte, acetylene black as a conductive additive, and styrene-butadiene rubber (SBR) as a binder were prepared. In a glove box with an argon atmosphere with a dew point of -68℃ or less, the NMC composite oxide, the solid electrolyte, and acetylene black were weighed out to a mass ratio of 83.8:10.8:5.4, mixed in an agate mortar, and further mixed and stirred in a planetary ball mill. 2.7 parts by mass of styrene-butadiene rubber (SBR) were added to 100 parts by mass of the obtained mixed powder, and xylene was added as a solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry prepared above was applied to one surface of an aluminum foil (thickness: 20 μm) serving as a positive electrode current collector, and then dried to form a positive electrode active material layer (area weight: 25.0 mg / cm 2 ) was formed to prepare a positive electrode.
[0074] (Preparation of solid electrolyte layer) An argyrodite-type solid electrolyte (Li6PS5Cl, average particle size (D50) 3 μm), which is a lithium ion conductive halogen-containing sulfide solid electrolyte, and SBR, which is a binder, were mixed in a mass ratio of 95:5, and an appropriate amount of xylene was added as a solvent and mixed to prepare a solid electrolyte slurry. The solid electrolyte slurry prepared above was applied to one surface of stainless steel (SUS430LX) foil (thickness 10 μm) as a negative electrode current collector, and dried to form a solid electrolyte layer (basis weight 3.7 mg / cm 2 After pressing, the thickness was 20 μm.
[0075] (Preparation of test cell) The solid electrolyte layer prepared above was transferred to the exposed surface of the positive electrode prepared above by cold isostatic pressing (CIP). An aluminum positive electrode tab and a nickel negative electrode tab were bonded to the aluminum foil as the positive electrode current collector and the stainless steel foil as the negative electrode current collector, respectively, by an ultrasonic welding machine, and the resulting laminate was placed inside an aluminum laminate film and vacuum sealed to prepare a test cell.
[0076] <Charge / discharge test> [Example 1] The following charge / discharge test was carried out while applying a restraining pressure of 3 MPa to the test cell produced above in the stacking direction using a pressure member.
[0077] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 4.5%, charging was stopped and a rest period of 0.02h was allowed. After that, the current density was 0.04mA / cm 2 The cell was discharged at a constant current (equivalent to 0.01 C), and when the voltage reached 2.5 V, the discharge was stopped and the cell was left in a rest state for 0.5 h. As a result, a Li layer made of metallic lithium was formed on the surface of the negative electrode current collector facing the solid electrolyte layer.
[0078] (Second charging process) Next, the current density is 0.22mA / cm 2 The battery was charged at a constant current (equivalent to 0.05C), and when the voltage reached 4.2V, charging was switched to constant voltage mode, with the current value set at 0.04mA / cm 2 (equivalent to 0.01C) charging was stopped. With the above operations, charging of the test cell was completed.
[0079] (Measurement of average charge / discharge efficiency) After the second charging step, a rest period of 0.5 h was carried out. Then, the current density was 0.22 mA / cm 2Discharging of the battery was started at a constant current (equivalent to 0.05C), and was stopped when the voltage reached 2.5V. The percentage of the discharged charge relative to the charged charge ((discharged charge amount ÷ charged charge amount) × 100) was calculated to determine the charge / discharge efficiency (%). The charge / discharge efficiency (%) was determined for each of the five test cells (N=5), and the average value was determined to be the average charge / discharge efficiency (%). In cases where the average charge / discharge efficiency (%) was less than 80%, it was determined that a micro-short circuit had occurred.
[0080] [Example 2] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0081] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 3.0%, charging was stopped and a rest period of 0.02h was allowed. After that, the current density was 0.04mA / cm 2 The cell was discharged at a constant current (equivalent to 0.01 C), and when the voltage reached 2.5 V, the discharge was stopped and the cell was left in a rest state for 0.5 h. As a result, a Li layer made of metallic lithium was formed on the surface of the negative electrode current collector facing the solid electrolyte layer.
[0082] [Example 3] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0083] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 1.5%, charging was stopped and a rest period of 0.02h was allowed. After that, the current density was 0.04mA / cm 2The cell was discharged at a constant current (equivalent to 0.01 C), and when the voltage reached 2.5 V, the discharge was stopped and the cell was left in a rest state for 0.5 h. As a result, a Li layer made of metallic lithium was formed on the surface of the negative electrode current collector facing the solid electrolyte layer.
[0084] [Example 4] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0085] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 1.5%, charging was stopped and a rest period of 0.02h was allowed. After that, the current density was 0.04mA / cm 2 The cell was discharged at a constant current (equivalent to 0.01 C), and when the voltage reached 2.5 V, the discharge was stopped and a 0.5-h pause was performed. This cycle was repeated five times. As a result, a deposited Li layer made of metallic lithium was formed on the solid electrolyte layer side surface of the negative electrode current collector.
[0086] [Example 5] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0087] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 1.5%, charging was stopped and a rest period of 0.02h was allowed. After that, the current density was 0.04mA / cm 2The cell was discharged at a constant current (equivalent to 0.01C), and when the voltage reached 0V, the discharge was stopped and a 0.5-h pause was performed. This cycle was repeated 5 times. As a result, a deposited Li layer made of metallic lithium was formed on the surface of the negative electrode current collector facing the solid electrolyte layer.
[0088] [Example 6] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0089] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 1.5%, charging was stopped and a rest period of 1.5h was allowed. After that, the current density was 0.04mA / cm 2 The cell was discharged at a constant current (equivalent to 0.01 C), and when the voltage reached 2.5 V, the discharge was stopped and a 0.5-h pause was performed. This cycle was repeated five times. As a result, a deposited Li layer made of metallic lithium was formed on the solid electrolyte layer side surface of the negative electrode current collector.
[0090] [Example 7] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0091] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 0.01C (equivalent to 0.01C), and when the SOC reached 1.5%, charging was stopped and a rest period of 0.02h was allowed. After that, the current density was 0.04mA / cm 2The cell was discharged at a constant current (equivalent to 0.01 C), and when the voltage reached 2.5 V, the discharge was stopped and a 0.5-h pause was performed. This cycle was repeated 10 times. As a result, a deposited Li layer made of metallic lithium was formed on the surface of the negative electrode current collector facing the solid electrolyte layer.
[0092] [Example 8] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0093] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current of 10 ...
[0094] [Example 9] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0095] (First charging process) The test cell was left in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.04 mA / cm 2 The cell was charged at a constant current (equivalent to 0.01C), and after a certain time (0.296h) had elapsed (when the SOC had increased by 0.3%), charging was stopped and a 0.02h pause was performed. This charging and pause operation was repeated five times (the SOC reached 1.5% after the fifth charge, after which a 0.02h pause was performed). As a result, a Li layer made of metallic lithium was formed on the solid electrolyte layer side surface of the negative electrode current collector.
[0096] [Example 10] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) and (second charging step) were carried out in the following manner.
[0097] (First charging process) The test cell was placed in a thermostatic chamber at 60° C. for 5 hours to set the cell temperature to 60° C. Next, a first current density I1 was set at a current density of 0.21 mA / cm 2 The cell was charged at a constant current of 0.048 C, and when the SOC reached 1.5%, charging was stopped and a 0.02-h pause was performed. This resulted in the formation of a Li layer made of metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector.
[0098] (Second charging process) Next, the current density is 0.87mA / cm 2 The battery was charged at a constant current (equivalent to 0.2C), and when the voltage reached 4.2V, charging was switched to constant voltage mode with a current value of 0.04mA / cm 2 (equivalent to 0.01C) charging was stopped. With the above operations, charging of the test cell was completed.
[0099] [Comparative Example 1] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0100] (First charging process) The test cell was placed in a thermostatic chamber at 60° C. for 5 hours to set the cell temperature to 60° C. Next, a first current density I1 was set at a current density of 0.87 mA / cm 2 The cell was charged at a constant current of 0.20 C, and the charging was stopped when the SOC reached 1.5%. This resulted in the formation of a Li layer made of metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector.
[0101] [Comparative Example 2] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0102] (First charging process) The test cell was placed in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 4.37 mA / cm 2 The cell was charged at a constant current (equivalent to 1.00 C) and stopped charging when the SOC reached 1.5%. This resulted in the formation of a deposited Li layer made of metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector.
[0103] [Comparative Example 3] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0104] (First charging process) The test cell was placed in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set to a current density of 0.43 mA / cm 2 The cell was charged at a constant current of 0.10 C, and when the SOC reached 1.5%, charging was stopped and a 0.02-h pause was performed. This resulted in the formation of a Li layer made of metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector.
[0105] [Comparative Example 4] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0106] (First charging process) The test cell was placed in a thermostatic chamber at 60° C. for 5 hours to bring the cell temperature to 60° C. Next, a first current density I1 was set at a current density of 0.22 mA / cm 2 The cell was charged at a constant current of 0.05 C, and when the SOC reached 1.5%, charging was stopped and a 0.02-h pause was performed. This resulted in the formation of a Li layer made of metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector.
[0107] [Comparative Example 5] A charge / discharge test was carried out in the same manner as in Example 1, except that the above (first charging step) was carried out in the following manner.
[0108] (First charging process) The test cell was placed in a thermostatic chamber at 60° C. for 5 hours to set the cell temperature to 60° C. Next, a first current density I1 was set at a current density of 0.87 mA / cm 2 The cell was charged at a constant current of 0.20 C, and when the SOC reached 30%, charging was stopped and a 0.02-h pause was performed. This resulted in the formation of a Li layer made of metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector.
[0109] The results are shown in Table 1 below.
[0110] [Table 1]
[0111] From the results shown in Table 1, it is evident that according to the present invention, short circuits in secondary batteries can be further suppressed.
[0112] This application is based on Japanese Patent Application No. 2021-212284, filed on December 27, 2021, the disclosure of which is hereby incorporated by reference in its entirety. [Explanation of symbols]
[0113] 10a Stacked battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film.
Claims
1. A method for charging a secondary battery having a positive electrode current collector, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector in this order, the method utilizing a deposition-dissolution reaction of metallic lithium as a reaction at the negative electrode, comprising the steps of: a first charging step of charging the secondary battery at a first current density I1 to deposit metallic lithium on the solid electrolyte layer side surface of the negative electrode current collector, thereby forming a deposited Li layer which is a part of the negative electrode active material layer and is made of the metallic lithium; After the first charging step, the secondary battery is charged at a second current density I2 greater than the first current density I1 to increase the thickness of the deposited Li layer. The method for charging a secondary battery has a multi-stage charging process, in which the first charging step includes at least one rest or at least one discharge, and the secondary battery is charged at the first current density I1 so that the SOC does not exceed 4.5%, and the first current density I1 is less than 0.22 (mA / cm2).
2. the first charging step includes at least one pause; 2. The method for charging a secondary battery according to claim 1, wherein the pause time is 1.5 hours or less.
3. The first charging step includes at least one discharge; 3. The method for charging a secondary battery according to claim 1, wherein an end-of-discharge voltage in the discharging is 2.5 V or less.
Citation Information
Patent Citations
Method of charging nonaqueous electrolyte battery
JP2003109672A
Lithium solid type secondary battery and method for manufacturing the same
JP2016035867A
Method for charging secondary battery
JP2020009724A
Method for charging secondary cell and charger
WO2000042673A1
Secondary battery charging method and charging system
WO2022065088A1